Ammonium natural attenuation in complex hydrogeological settings: insights from a multi-isotope approach - Caschetto, Mariachiara (Acque Sotterranee - Italian Journal of Groundwater, 2017)
A full methodology including a multi-isotopic approach coupled with depth-dependent groundwater sampling is here reported to investigate the occurrence of ammonium natural attenuation. Examples from three hydrogeological settings, representative of different environmental issues in relation to nitrate and ammonium pollution are here reported: a septic system plume (SSP), where the discharging effluent composition into a shallow aquifer is dominantly ammonium-based; a Groundwater Dependent Ecosystem (GDE), where river waters are impacted by upwelling of anthropogenic and natural ammonium negatively affecting the ecosystem's functionality, and an alluvial coastal aquifer (ACA) affected by abnormal natural ammonium concentrations along with a high content of other undesired compounds. Several sampling methodologies were applied for depth-dependent groundwater sampling such as multi-level nested wells, straddle packers system, and common long screen wells. Such detailed sampling techniques were coupled with a multi-isotopic approach. Environmental isotopes (Î´18O and Î´D in H2O) were used to gain insights into the hydrogeological flow system while other stable isotopes Î´15NNH4, Î´15NNO3, Î´18ONO3 were purposefully applied for the identification of N compounds' source(s), fate and processes. In addition, Î´34SSO4, Î´18OSO4, and Î´13CDIC were proposed as tools for understanding the potential attenuation processes in relation to the other biogeochemical cycles. Tritium data was also applied for recharge rate and groundwater residence time estimation. The adopted approach helped reaching site-specific insights into the hydrogeological and geochemical conceptual models. In SSP, the isotopic evidence of anammox occurrence, together with denitrification and nitrification processes, result to be responsible of the 60-80% of the total N removal at the distal portion of the plume; in GDE, ammonium and nitrate, coming mainly from agricultural practices, affect the deep and the shallow flow systems. Ammonium results to be locally attenuated by dilution and nitrification. In ACA, the major ammonium pool derives from the low-lying aquitard as a biogenic source while anthropogenic minor inputs (NH4+ and NO3 -) from the shallow circulation in the aquifer were also identified. NH4+ resulted attenuated by transport processes and partial nitrification processes. Moreover, by the use of a multiisotope approach sound evidence of the anaerobic oxidation of methane coupled with SO42- reduction has been arisen. The overview provided by the proposed case studies put emphasis on the importance of the identification of reliable conceptual models which cluster physical patterns (e.g. groundwater flow) together with chemical and isotopic data, representing a fundamental step in the integration of the groundwater and the nitrogen cycles, thereby of high concern for sustainable water management and best practices.